Consumer Confidence and Asset Prices: Some Empirical Evidence - Lemmon, Michael; Portniaguina, Evgenia (Review of Financial Studies, 2006)
We explore the time-series relationship between investor sentiment and the small-stock premium using consumer confidence as a measure of investor optimism. We estimate the components of consumer confidence related to economic fundamentals and investor sentiment. After controlling for the time variation of beta, we study the time-series variation of the pricing error with sentiment. Over the last 25 years, investor sentiment measured using consumer confidence forecasts the returns of small stocks and stocks with low institutional ownership in a manner consistent with the predictions of models based on noise-trader sentiment. Sentiment does not appear to forecast time-series variation in the value and momentum premiums.